Participation in the determination of a model for social responsibility in the mining sector - Arias Arce, Vladimir (2012)
The challenge of a development model that seeks to harmonize economic, social and environmental issues requires appropriate governance structures to address this complexity, as well as an active participation of citizens in public issues. Participation of civil society in development decisions is crucial to achieving lasting and sustainable solutions. Modern democratic life requires an increasingly active role of the population, community members involvement is required, and citizens should not be allowed to act only when it comes to choosing, and be therefore governed by others, without any possibility of interacting with the ruling people. Now the concept of representative democracy is swifting into a different hue of what is called participatory democracy. In order to move forward to build a participatory democracy, it is necessary to provide citizens with an institutional framework that facilitates effective exercise of participation in the management and activities of public interest.